Modified fluorine-containing gypsum, modified fluorine-containing gypsum product and its manufacturing method

By mixing and grinding lime with silica fluoride and adding nanphenol-based water reducer, the problems of low grinding efficiency and strong acidity of silica fluoride are solved, and its efficient use and large-scale application as a gel material are achieved.

JP2025514258AActive Publication Date: 2025-05-02HENAN POLYTECHNIC UNIV
View PDF 15 Cites 0 Cited by

Patent Information

Application Number
JP2024563469
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-06-12
Filing Date
2024-01-31
Publication Date
2025-05-02
Estimated Expiration
2044-01-31

AI Technical Summary

Technical Problem

In the prior art, the grinding efficiency of fluoride silica is low, highly acidic and poorly active, which limits the scale of its direct use as a gel material. The accumulation treatment occupies a large amount of land and wastes resources. The long-term accumulation of harmful substances such as acidic and soluble F will gradually leak, resulting in soil and groundwater pollution.

Method used

The activity and mechanical properties of the fluoride silica are improved by mixing lime (CaO) with silica fluoride, adding a nanophenol-based water reducer, and controlling the mass ratio and grinding time of lime and silica fluoride.

Benefits of technology

The improved silica fluoride not only improves its performance as a gel material, reduces the release of fluoride ions, realizes large-scale use of silica fluoride, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025514258000001_ABST
    Figure 2025514258000001_ABST
Patent Text Reader

Abstract

Modified fluorine-containing gypsum, modified fluorine-containing gypsum product and method for producing the same. [Solution] The manufacturing method of modified fluorine-containing gypsum includes a step of mixing and grinding quicklime and fluorine-containing gypsum, and a step of adding a naphthalene-based water reducing agent, in which the mass ratio of quicklime to fluorine-containing gypsum is (0.5-1.0):100, the mass ratio of the naphthalene-based water reducing agent to fluorine-containing gypsum is (0.3-0.9):100, and the mixing and grinding time is 15-45 minutes. In response to the problems that exist in directly using fluorine-containing gypsum as a gelling material, the present invention proposes a method of modifying it using quicklime and a naphthalene-based water reducing agent, which is low cost, easy to implement, suitable for industrialized production, and uses a single raw material with a small variety.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention belongs to the field of building materials technology, and particularly relates to modified fluorine-containing gypsum, modified fluorine-containing gypsum products and methods for producing the same. [Background technology]

[0002] Fluorine-containing gypsum is a slag generated when hydrofluoric acid is produced in a fluoride salt factory using fluorite and concentrated sulfuric acid. Its main chemical composition is anhydrous calcium sulfate (type 2), with a certain amount of residual calcium fluoride, sulfuric acid, hydrofluoric acid, a small amount of silica, and a trace amount of Na. + , K + It contains impurities such as

[0003] Fluorine-containing gypsum has problems such as low grinding efficiency, strong acidity, and poor activity, which restrict its direct use as a gelling material, thereby limiting its large-scale use. The current treatment of fluorine-containing gypsum is still mainly done by stacking, which not only occupies a large amount of land, but also is a huge waste of resources. In addition, the acidic and soluble F contained in the fluorine-containing gypsum that has been stacked for a long time - Toxic and harmful substances such as fluorine will gradually seep out, causing serious pollution of the surrounding soil and groundwater. Fluorine-containing gypsum has a low density, and the dust blown by the wind also has a significant impact on the air and the environment. In recent years, standard stacking has been basically carried out in various places, but the high maintenance costs of stacking sites not only reduce the economic benefits of companies, but also become an important factor restricting the sustainable development of companies.

[0004] At present, fluorine-containing gypsum is mainly used as an auxiliary gelling material or as a gelling inhibitor for cement in place of natural gypsum dihydrate, and the resource utilization rate is relatively low.

[0005] Therefore, there is a need to provide an improved technical solution to address the shortcomings of the prior art. Summary of the Invention [Problem to be solved by the invention]

[0006] An object of the present invention is to provide a modified fluorine-containing gypsum, a modified fluorine-containing gypsum product and a method for producing the same, in order to solve or alleviate the problems existing in the prior art. [Means for solving the problem]

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] A step of co-grinding quicklime and fluorine-containing gypsum; further adding a naphthalene-based water reducing agent; A method for producing a modified fluorine-containing gypsum, comprising: a mass ratio of the quicklime to the fluorine-containing gypsum is (0.5 to 1.0):100, and a mass ratio of the naphthalene-based water-reducing agent to the fluorine-containing gypsum is (0.3 to 0.9):100, The method for producing modified fluorine-containing gypsum, wherein the mixing and grinding time is 15 to 45 minutes.

[0009] A modified fluorine-containing gypsum produced by the above-mentioned production method.

[0010] A modified fluorine-containing gypsum product, which is produced using the modified fluorine-containing gypsum described above.

[0011] The above-mentioned method for producing the modified fluorine-containing gypsum product includes the steps of: (1) stirring and uniformly mixing the modified fluorine-containing gypsum with water to obtain a modified fluorine-containing gypsum slurry; and (2) putting the modified fluorine-containing gypsum slurry into a mold and curing it to obtain the modified fluorine-containing gypsum product. Beneficial effects

[0012] In response to the problems inherent in directly using fluorine-containing gypsum as a gelling material, the present invention proposes a method for modifying fluorine-containing gypsum using quicklime and a naphthalene-based water-reducing agent, which is low-cost, easy to implement, suitable for industrialized production, and requires only a single raw material and a small variety.

[0013] By mixing fluorine-containing gypsum with a certain proportion of quicklime and a naphthalene-based water reducing agent and then grinding (polishing), the grinding efficiency is increased, the hydration activity of the fluorine-containing gypsum is increased, and the elution of fluorine ions is effectively suppressed. The modified fluorine-containing gypsum of the present invention can be directly used as a gelling material, realizing large-scale resource utilization of fluorine-containing gypsum. [Brief description of the drawings]

[0014] [Figure 1] FIG. 2 is a diagram showing the effect of the amount of quicklime mixed in according to an embodiment of the present invention on the pH value of fluorine-containing gypsum. [Diagram 2] FIG. 1 is a diagram of the effect of grinding time on the particle size distribution of modified fluorinated gypsum particles, where (a) is the particle size distribution and (b) is the cumulative volume. [Diagram 3] SEM images of fluorine-containing gypsum after 15 minutes of grinding, (a) without quicklime mixed in, and (b) with 0.75% quicklime mixed in. [Figure 4] FIG. 2 is a comparative XRD diagram of modified fluorine-containing gypsum obtained by pulverization for 15 minutes according to Example 2 and pulverized fluorine-containing gypsum according to Comparative Example 1. [Diagram 5] FIG. 1 shows the effect of the amount of water-reducing agent added on the particle size distribution of modified fluorine-containing gypsum, where (a) is the particle size distribution and (b) is the cumulative volume. [Figure 6] FIG. 1 is a graph showing the setting time and standard consistency water consumption results of modified fluorine-containing gypsum with different amounts of water-reducing agent mixed in. [Figure 7] FIG. 2 is a diagram of the flexural strength of modified fluorinated gypsum products with different hydration times. [Figure 8] FIG. 1 is a graph of compressive strength of modified fluorine-containing gypsum products with different hydration times. [Figure 9]13 shows images of modified fluorinated gypsum products with different amounts of water-reducing agent during 3 days of hydration. [Figure 10] FIG. 2 is a graph showing the hydration rate results of modified fluorine-containing gypsum with different amounts of water-reducing agent. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The present invention provides a method for producing modified fluorine-containing gypsum, which is a solution to the problems of current fluorine-containing gypsum being inappropriate for direct use as a gelling material and difficult to utilize as a resource on a large scale. The method for producing modified fluorine-containing gypsum includes a step of mixing and grinding quicklime and fluorine-containing gypsum.

[0016] In the process of mixing and grinding quicklime and fluorine-containing gypsum, quicklime can play the role of grinding assistant, which is helpful in improving the grinding effect of fluorine-containing gypsum, reducing the particle size of fluorine-containing gypsum, and making the particle size of the obtained modified fluorine-containing gypsum more uniform. Quicklime can also adjust the pH and free F. - By acting as setting ions, they also help improve the mechanical performance and hydration rate of modified fluorinated gypsum products.

[0017] Further, the method includes adding a naphthalene-based water reducing agent, which can also play the role of grinding aid in the grinding process of fluorine-containing gypsum, shorten the setting time of the modified fluorine-containing gypsum, and reduce the standard consistency water consumption, which is helpful in improving the mechanical properties of the modified fluorine-containing gypsum product and improving the hydration rate.

[0018] The mass ratio of quicklime to fluorine-containing gypsum is (0.5~1.0):100 (e.g., 0.5:100, 0.6:100, 0.7:100, 0.8:100, 0.9:100, or 1.0:100). The mass ratio of naphthalene-based water-reducing agent to fluorine-containing gypsum is (0.3~1.5):100 (e.g., 0.3:100, 0.5:100, 0.7:100, 0.9:100, 1.1:100, 1.2:100, 1.3:100, 1.4:100, or 1.5:100).

[0019] The mass ratio of the naphthalene-based water reducing agent to the fluorine-containing gypsum is (0.3-0.9):100 (for example, 0.4:100, 0.6:100, or 0.8:100). When the mass ratio of the naphthalene-based water reducing agent to the fluorine-containing gypsum is (0.3-0.9):100, the modified fluorine-containing gypsum product has a flat surface, no obvious cracks, and good mechanical properties and volume stability.

[0020] The mass ratio of quicklime to fluorine-containing gypsum is 0.75:100, and the mass ratio of the naphthalene-based water-reducing agent to fluorine-containing gypsum is 0.9:100.

[0021] Fluorine-containing gypsum is a by-product generated during the production of hydrogen fluoride. It has a particle size of 0.3-1.5cm, a pH value of 2.3, and a density of 2.59g / cm. 3 The main mineral composition of fluorine-containing gypsum is type 2 anhydrite, and fluorine-containing gypsum also contains fluorite.

[0022] The effective calcium oxide content of the quicklime is 80 wt.% or more, and the naphthalene-based water-reducing agent is a commercially available naphthalene-based water-reducing agent.

[0023] The mixed grinding is carried out in a ball mill, and the mixed grinding time is 15 to 45 minutes (for example, 15 minutes, 20 minutes, 25 minutes, 30 minutes, 35 minutes, 40 minutes, or 45 minutes).

[0024] The ball mill is a Φ50cm×50cm ball mill.

[0025] A modified fluorine-containing gypsum produced by the above-mentioned production method.

[0026] A modified fluorine-containing gypsum product, which is produced using the modified fluorine-containing gypsum described above.

[0027] A method for producing a modified fluorine-containing gypsum product, comprising: a step (1) of uniformly mixing the modified fluorine-containing gypsum with water by stirring to obtain a modified fluorine-containing gypsum slurry; and a step (2) of putting the modified fluorine-containing gypsum slurry into a mold and curing the mold to obtain a modified fluorine-containing gypsum product.

[0028] Curing is performed at a temperature of 20±5°C (e.g., 15°C, 18°C, 20°C, 22°C, 24°C, or 25°C) and a relative humidity of 70%±4% (e.g., 66%, 68%, 70%, 72%, or 74%).

[0029] The modified fluorine-containing gypsum and its manufacturing method, and the modified fluorine-containing gypsum product and its manufacturing method of the present invention will be described in detail below with reference to specific examples.

[0030] In the following examples, the fluorine-containing gypsum used is a by-product generated during the production of hydrogen fluoride. The gray-white spherical particles have a particle size of 0.3 to 1.5 cm, a pH value of 2.3, and a density of 2.59 g / cm. 3 Its main mineral composition is type II anhydrite, with small amounts of residual fluorite.

[0031] Quicklime is quicklime powder, and its technical requirements meet the relevant requirements of the industry standard "Quicklime Powder for Construction" (JC / T480-92) and above.

[0032] The naphthalene-based water reducing agent is a commercially available powder and is a brown powder.

[0033] Example 1 The method for producing the modified fluorine-containing gypsum of this embodiment includes the steps of mixing 100 parts of fluorine-containing gypsum with 0.5 parts, 0.75 parts, 1.0 parts, and 1.5 parts of quicklime, respectively, in parts by mass, and placing the mixture in a Φ50 cm×50 cm ball mill to pulverize for 15 minutes to obtain the modified fluorine-containing gypsum of this embodiment.

[0034] The method for producing the modified fluorine-containing gypsum product of this embodiment is as follows: Step (1), in which water and powdery modified fluorine-containing gypsum of this embodiment are respectively referred to as the modified fluorine-containing gypsum of this embodiment are sequentially charged into a stirring kettle at a set water-to-material ratio, uniformly mixed and stirred to obtain a modified fluorine-containing gypsum slurry, the amount of water used in the manufacturing process of the modified fluorine-containing gypsum slurry is determined based on the standard consistency water usage, and when the amount of quicklime used is 0.5 parts, 0.75 parts, 1.0 parts and 1.5 parts, the corresponding water-to-material ratios are 0.28, 0.31, 0.32 and 0.327, respectively; Step (2) of placing the modified fluorine-containing gypsum slurry in step (1) into a mold having a preset specification, and carrying out a test of the setting time and compressive strength, respectively; and (3) testing the setting time and compressive strength of the gypsum slurry using a Vicat apparatus in accordance with the national standard "PLASTERER GYPSUM" (GB / T 28627-2012). The mechanical performance test specimen of the hardened slurry has a size of 40mm x 40mm x 160mm and is cured under the following conditions: temperature is 20±5°C, relative humidity (RH) is 70%±4%. The flexural strength and compressive strength are tested at 3d, 7d, and 28d, respectively. Each group tests three specimens, and the average value is used as the final result.

[0035] The pH of the fluorine-containing gypsum and the modified fluorine-containing gypsum prepared in this embodiment were measured respectively to determine the effect of quicklime content on the pH of the fluorine-containing gypsum. The experimental results are shown in FIG. 1.

[0036] As is clear from FIG. 1, quicklime was externally mixed into the fluorine-containing gypsum in amounts of 0.5%, 0.75%, 1.0%, and 1.5% of the mass of the fluorine-containing gypsum, respectively, and the pH of the modified fluorine-containing gypsum produced increased with an increase in the amount of quicklime mixed in. When the amount of quicklime mixed in was 0.75%, the pH value reached neutral, being 7.3.

[0037] Example 2 The method for producing the modified fluorine-containing gypsum of this embodiment includes the steps of mixing, by mass, 100 parts of fluorine-containing gypsum with 0.75 parts of quicklime, placing the mixture in a Φ50 cm×50 cm ball mill, and pulverizing the mixture for 15 minutes, 30 minutes, and 45 minutes, respectively, to obtain the modified fluorine-containing gypsum of this embodiment.

[0038] The method for producing the modified fluorine-containing gypsum product of this embodiment is as follows: Step (1), in which water and powdery modified fluorine-containing gypsum of this embodiment are respectively referred to as modified fluorine-containing gypsum of the present embodiment are sequentially charged into a stirring kettle at a set water / material ratio, uniformly mixed and stirred to obtain modified fluorine-containing gypsum slurry, the water consumption in the manufacturing process of the modified fluorine-containing gypsum slurry is determined based on the standard consistency water consumption, and the water / material ratios corresponding to the grinding times of 15 min, 30 min, and 45 min are 0.31, 0.35, and 0.38, respectively; Step (2) of placing the modified fluorine-containing gypsum slurry in step (1) into a mold having a preset specification, and carrying out a test of the setting time and compressive strength, respectively; Step (3) for testing the setting time and compressive strength, the setting time of the gypsum slurry is tested using a Vicat device in accordance with the national standard "Plastering Gypsum" (GB / T 28627-2012), the specifications of the mechanical performance test specimen of the hardened slurry are 40mm x 40mm x 160mm, the curing conditions are temperature 20±5°C, relative humidity (RH) 70%±4%, and the flexural strength and compressive strength are tested at 3d, 7d, and 28d respectively, with each group testing three specimens, and the average value is the final result.

[0039] Example 3 The method for producing the modified fluorine-containing gypsum of this embodiment includes the steps of mixing, by mass, 100 parts of fluorine-containing gypsum with 0.75 parts of quicklime and 0.3 parts, 0.6 parts, 0.9 parts, 1.2 parts, and 1.5 parts of a naphthalene-based water reducing agent, placing the mixture in a Φ50 cm×50 cm ball mill, and pulverizing the mixture for 15 minutes to obtain the modified fluorine-containing gypsum of this embodiment.

[0040] The method for producing the modified fluorine-containing gypsum product of this embodiment is as follows: Step (1), in which water and powdery modified fluorine-containing gypsum of this embodiment are respectively referred to as modified fluorine-containing gypsum of the present embodiment are sequentially charged into a stirring kettle at a set water / material ratio, uniformly mixed and stirred to obtain modified fluorine-containing gypsum slurry, the amount of water used in the manufacturing process of the modified fluorine-containing gypsum slurry is determined based on the standard consistency water usage, and when the amount of naphthalene-based water reducer used is 0.3 parts, 0.6 parts, 0.9 parts, 1.2 parts and 1.5 parts, the corresponding water / material ratios are 0.396, 0.382, 0.37, 0.312 and 0.232, respectively; Step (2) of placing the modified fluorine-containing gypsum slurry in step (1) into a mold having a preset specification, and carrying out a test of the setting time and compressive strength, respectively; Step (3) for testing the setting time and compressive strength, the setting time of the gypsum slurry is tested using a Vicat device in accordance with the national standard "Plastering Gypsum" (GB / T 28627-2012), the specifications of the mechanical performance test specimen of the hardened slurry are 40mm x 40mm x 160mm, the curing conditions are temperature 20±5°C, relative humidity (RH) 70%±4%, and the flexural strength and compressive strength are tested at 3d, 7d, and 28d respectively, with each group testing three specimens, and the average value is the final result.

[0041] Comparative Example 1 The method for producing the ground fluorine-containing gypsum of this comparative example includes a step of placing 100 parts by mass of fluorine-containing gypsum in a Φ50 cm × 50 cm ball mill and grinding it for 15 minutes to obtain the ground fluorine-containing gypsum of this comparative example.

[0042] The method for producing the ground fluorine-containing gypsum product of this comparative example is as follows: Step (1): water and powdered fluorine-containing gypsum of this comparative example are sequentially charged into a stirring kettle at a set water / material ratio (0.2), and then uniformly mixed and stirred to obtain a pulverized fluorine-containing gypsum slurry; Step (2) of placing the ground fluorine-containing gypsum slurry in step (1) into a mold having a preset specification, and carrying out a test for setting time and compressive strength, respectively; Step (3) for testing the setting time and compressive strength, the setting time of the gypsum slurry is tested using a Vicat device in accordance with the national standard "Plastering Gypsum" (GB / T 28627-2012), the specifications of the mechanical performance test specimen of the hardened slurry are 40mm x 40mm x 160mm, the curing conditions are temperature 20±5°C, relative humidity (RH) 70%±4%, and the flexural strength and compressive strength are tested at 3d, 7d, and 28d respectively, with each group testing three specimens, and the average value is the final result.

[0043] Comparative Example 2 The comparative example includes a step of modifying fluorine-containing gypsum with a polycarboxylic acid-based water-reducing agent instead of a naphthalene-based water-reducing agent, mixing, by mass, 100 parts of fluorine-containing gypsum and 0.75 parts of quicklime with 0.3 parts of the polycarboxylic acid-based water-reducing agent, placing the mixture in a Φ50 cm×50 cm ball mill and pulverizing the mixture for 15 minutes, to obtain the modified fluorine-containing gypsum of the comparative example.

[0044] The method for producing the modified fluorine-containing gypsum product of this comparative example is as follows: Step (1) of sequentially adding water and powdered modified fluorine-containing gypsum of this comparative example to a stirring kettle with a set water / material ratio (0.26, determined based on the standard consistency water usage), uniformly mixing and stirring to obtain a modified fluorine-containing gypsum slurry; Step (2) of placing the modified fluorine-containing gypsum slurry in step (1) into a mold having a preset specification, and carrying out a test of the setting time and compressive strength, respectively; Step (3) for testing the setting time and compressive strength, the setting time of the gypsum slurry is tested using a Vicat device in accordance with the national standard "Plastering Gypsum" (GB / T 28627-2012), the specifications of the mechanical performance test specimen of the hardened slurry are 40mm x 40mm x 160mm, the curing conditions are temperature 20±5°C, relative humidity (RH) 70%±4%, and the flexural strength and compressive strength are tested at 3d, 7d, and 28d respectively, with each group testing three specimens, and the average value is the final result.

[0045] Experimental Example 1. The particle size distribution of the modified fluorine-containing gypsum produced in Example 2 and the ground fluorine-containing gypsum produced in Comparative Example 1 was measured; The particle size distribution diagram is as shown in FIG. 2 and the particle size characterization parameters are as shown in Table 1 below.

[0046] [Table 1] Table 1: Particle size characterization of modified fluorine-containing gypsum and ground fluorine-containing gypsum

[0047] As can be seen from Figure 2 and Table 1, the incorporation of quicklime during the 15-min grinding process clearly reduced the particle size of the fluorine-containing gypsum and increased the D v (90) was reduced from 176 μm to 60.2 μm, improving the grinding efficiency. Quicklime exerted a good grinding-aid dispersion effect. However, with the increase in grinding time, small particles gradually aggregated due to the collision extrusion of the grinding body, and the particle size gradually increased.

[0048] 2. The micromorphology of the modified fluorine-containing gypsum (with 0.75% lime mixed in) produced by pulverizing for 15 min in Example 2 and the pulverized fluorine-containing gypsum (without lime mixed in) produced by pulverizing for 15 min in Comparative Example 1 was observed, and the XRD patterns, main chemical compositions, and soluble F of both were obtained. - The content was measured.

[0049] The SEM images of the modified fluorine-containing gypsum (containing 0.75% lime) produced by pulverization for 15 min in Example 2 and the pulverized fluorine-containing gypsum (containing no lime) produced by pulverization for 15 min in Comparative Example 1 are shown in Fig. 3(b) and Fig. 3(a), respectively, and the XRD patterns are shown in Fig. 4. The chemical compositions and soluble F - The contents were as shown in Table 3 below.

[0050] [Table 3] Table 3: Main chemical composition / wt.% of modified fluorine-containing gypsum ground for 15 min in Example 2 and ground fluorine-containing gypsum ground for 15 min in Comparative Example 1

[0051] As can be seen from Figure 3, the addition of quicklime made the particle size of the fluorine-containing gypsum after grinding more uniform, the particle surface was rough, and the shape was inclined to be spherical.

[0052] As can be seen from Fig. 4, the diffraction peaks of the fluorine-containing gypsum characterization after grinding were obviously enhanced, and the crystal grain size and structural regularity were also significantly improved by the grinding auxiliary effect of quicklime. At the same time, the diffraction peaks of fluorite were significantly enhanced, and the content of fluorine-containing gypsum was improved from 3.63% to 8.48%, and the improvement of the fluorite content was also favorable to the grinding of fluorine-containing gypsum.

[0053] From Table 3, the soluble F of the modified fluorine-containing gypsum - The ion content was reduced by 80.7%. The following reactions could occur during the grinding process: CaO+2H + +2F - →CaF2↓+H2O (1)

[0054] 3. The effect of quicklime on the performance of fluoride-containing gypsum was considered. (1) The setting and hardening performance of the modified fluorine-containing gypsum produced by pulverizing for 15 minutes in Example 2, in which the amount of quicklime mixed in was 0.75%, was compared with that of the pulverized fluorine-containing gypsum produced by pulverizing for 15 minutes in Comparative Example 1, in which no quicklime was mixed in. The test results are shown in Table 4 below.

[0055] [Table 4] Table 4: Comparison of the physical properties of fluorine-containing gypsum products obtained with and without quicklime mixing during grinding

[0056] Table 4 shows the effect of quicklime on the setting and hardening performance of fluorine-containing gypsum. The grinding-assisting effect of quicklime significantly reduced the particle size of fluorine-containing gypsum, resulting in an increase in the amount of standard consistency water used. Smaller particle size means that the specific surface area of ​​fluorine-containing gypsum is larger, which is favorable for the progress of the hydration reaction, increasing the hydration and hardening speed and shortening the setting time. The mechanical performance of fluorine-containing gypsum products is also improved, and the improving effect of quicklime on the strength of fluorine-containing gypsum products is more obvious at 28 days, which can suppress the occurrence of later strength regression of fluorine-containing gypsum products.

[0057] (2) The hydration rates of the modified fluorine-containing gypsum produced by pulverizing for 15 minutes in Example 2, in which the amount of quicklime mixed in was 0.75%, and the pulverized fluorine-containing gypsum produced by pulverizing for 15 minutes in Comparative Example 1 without adding quicklime, were measured. The measurement method was to test the hydration rate using a muffle furnace according to the national standard "Building gypsum - Determination of crystal water content" (GB / T17669.2-1999), and calculate the dihydrate gypsum content and the hydration rate of fluorine-containing gypsum. The test results are shown in Table 5 below.

[0058] [Table 5] Table 5: Comparison of hydration rates of fluorine-containing gypsum with and without quicklime mixing during grinding

[0059] The hydration rate of fluorine-containing gypsum also increased after mixing with quicklime grinding aid, as shown in Table 5. The hydration rate showed a small increase within 1 d, and the hydration rate increased significantly after 1 d of solidification. This law was consistent with the mechanical performance.

[0060] 4. Water reducers were a common additive in the application of gelling materials. Although the particle size distribution of fluorine-containing gypsum after grinding was smaller, it led to an increase in the amount of standard consistency water used, which was unfavorable to the development of performance. Grinding aids could not only improve the grinding efficiency of materials in the grinding process, but also reduce energy consumption and improve the performance of powder. Therefore, the effect of naphthalene-based water reducers as grinding aids on the performance of fluorine-containing gypsum was explored, and its grinding aid modification mechanism was clarified.

[0061] The particle size distribution of the modified fluorine-containing gypsum of Example 3 was measured, and the effects of different water-reducing agent contents on the particle size distribution of the fluorine-containing gypsum after grinding were as shown in FIG. 5 and Table 6 below.

[0062] [Table 6] Table 6: Effect of water reducers on the grinding aid effect of fluorine-containing gypsum

[0063] The results show that naphthalene-based water-reducing agents can play a "grinding aid" role in the grinding process of fluorine-containing gypsum. The particle size distribution of fluorine-containing gypsum is first optimized to gradually finer particles with increasing water-reducing agent content, and the distribution is more concentrated. When the water-reducing agent content is 0.6%, the particle size distribution reaches a minimum, and then the particle size increases as the excess water-reducing agent particles gradually aggregate. The specific surface area of ​​fluorine-containing gypsum particles also first increases and then decreases with increasing water-reducing agent content.

[0064] According to the results in Table 6, when the amount of water-reducing agent mixed is 0.6%, the fluorine-containing gypsum particles have a median diameter D v (90) decreased to 37.8 μm, and D v (50) is reduced to 3.76 μm, and D v (10) is reduced to 0.394 μm and the specific surface area is 472.1 m 2 / kg.

[0065] The presence of an appropriate amount of water reducing agent makes the mutual dispersion of fluorine-containing gypsum particles greater during the grinding process, and the water reducing agent gradually adheres to the particle surface, reducing the mutual extrusion collision between particles, and reducing the occurrence of particle aggregation and grinding phenomenon. However, if the water reducing agent is excessive within the same grinding time, the surface roughness increases, the specific surface area increases, and the surface energy increases, causing mutual mechanical interlocking, inducing the aggregation phenomenon, and is unfavorable to the grinding efficiency.

[0066] 5. The effect of naphthalene-based water-reducing agents on the solidification and hardening performance of modified fluorine-containing gypsum was considered. (1) Measure the standard consistency water requirement and setting time of the modified fluorine-containing gypsum with different amounts of water-reducing agent in Example 3; The grinding auxiliary effect of the water reducing agent increases the grinding efficiency of the fluorine-containing gypsum, so the standard consistency water consumption of the fluorine-containing gypsum slurry rises first and then decreases with the increase in the amount of water reducing agent, as shown in Figure 6. When the amount of water reducing agent is low, the fluorine-containing gypsum particles are further fragmented, and the water reducing agent adheres to the particle surface, which can increase the charge repulsion between particles, but the increase in the specific surface area causes an increase in the amount of water required. As the amount of water reducing agent gradually increases, the degree of dispersion between particles increases and the amount of water required decreases.

[0067] The setting time of fluorine-containing gypsum was shortened with an increase in the amount of water-reducing agent. When the amount of water-reducing agent was low, the particle size of fluorine-containing gypsum was finely divided, which increased the dissolution rate and the nucleation rate of gypsum dihydrate, accelerated the crystal precipitation and growth of gypsum dihydrate, and accelerated the hydration process, resulting in a shortened setting time. As the amount of water-reducing agent increased and the amount of standard consistency water used decreased, the gap between the slurry particles became smaller, and the hardened structure between the gypsum dihydrate after the hydration reaction was easily formed, resulting in a shortened setting time. The initial setting time and final setting time of the slurry were shortened from 421 min and 554 min in the control group to 104 min and 237 min, respectively, when the amount of water-reducing agent was 1.5%.

[0068] The water requirement and setting time were measured according to the national standard "Plastering Gypsum" (GB / T 28627-2012).

[0069] (2) Measuring the mechanical properties of the hardened fluorine-containing gypsum (modified fluorine-containing gypsum) at different times in Example 3; The mechanical properties of hardened fluorine-containing gypsum at different times tended to increase and then decrease with increasing amount of water-reducing agent, and both reached a maximum when the amount of water-reducing agent was 0.9%.

[0070] In Figure 7, the flexural strength of the fluorine-containing gypsum with a mixing amount of 0.9% increased from 1.9 MPa for the control group (the sample with 0 mixing amount of naphthalene-based water reducing agent, i.e., the sample numbered 1 in Table 6) to 5.4 MPa after 3 days of hydration, an increase of 184.2%. The flexural strength after 7 days of hydration increased from 5.2 MPa for the control group to 9.1 MPa, an increase of 75.0%. The flexural strength after 28 days of hydration increased from 7.9 MPa for the control group to 11.2 MPa, an increase of 41.8%.

[0071] In Fig. 8, the compressive strengths of the control group after 3 days, 7 days, and 28 days of hydration were 3.5 MPa, 7.6 MPa, and 10.0 MPa, respectively. When the amount of water-reducing agent mixed in was 0.9%, the compressive strengths of the fluorine-containing gypsum after 3 days, 7 days, and 28 days of hydration increased to 12.0 MPa, 21.1 MPa, and 28.9 MPa, respectively, which were increases of 243%, 178%, and 189%, respectively.

[0072] In FIG. 9, the samples were mixed with 0-0.9% water-reducing agent, and the surface of the modified fluorine-containing gypsum product was flat and had no obvious cracks during 3d of hydration. The samples were mixed with 1.2% and 1.5% water-reducing agent, and obvious cracks appeared on the surface of the modified fluorine-containing gypsum product during 3d of hydration. The larger the amount of water-reducing agent, the shorter the setting time of the fluorine-containing gypsum slurry and the easier it was for the fluorine-containing gypsum to form a hardened body structure. However, since the volume of the dihydrate gypsum crystals generated by hydration is much larger than that of the fluorine-containing gypsum, after forming a stable hardened body structure, with the continued progress of hydration, the dihydrate gypsum crystals continued to grow, and the internal volume constantly expanded, leading to the destruction of the hardened body structure, the volume stability was reduced, and the mechanical performance of the sample was also significantly reduced, until obvious cracks appeared on the sample surface. This was the main reason why the setting time of the fluorine-containing gypsum was shortened and the mechanical performance was reduced after the increase in the amount of water-reducing agent.

[0073] 6. The effect of naphthalene-based water reducers with different hydration times on the hydration rate of fluorine-containing gypsum was discussed. As shown in Figure 10, the effect of water-reducing agent on the hydration rate of fluorine-containing gypsum can be divided into two stages according to the hydration time. Before 3d of hydration, the hydration rate increased with the increase in the amount of water-reducing agent, and the hydration rate increased from 37.68% in the control group to 66.81% when the amount of water-reducing agent was 0.9%, and reached a maximum of 69.28% when the amount of water-reducing agent was 1.5%, which also conformed to the result law of setting time. The increase in the dissolution rate of fluorine-containing gypsum and the nucleation rate of dihydrate gypsum were the main reasons for the increase in the hydration rate.

[0074] After 3 d of hydration, the increase in the hydration rate of fluorine-containing gypsum with a water-reducing agent content of more than 0.9% became slow, while the hydration rate of fluorine-containing gypsum with a water-reducing agent content of less than 0.9% increased steadily. The hydration rate reached its maximum at 84.21% when the water-reducing agent content was 0.9% at 28 d. At this time, the hydration rates of the control group and the fluorine-containing gypsum with a water-reducing agent content of 1.5% were 45.37% and 75.71%, respectively. This result was consistent with the results of the mechanical properties. After the water-reducing agent content of fluorine-containing gypsum exceeded 0.9%, the cracks in the fluorine-containing gypsum sample caused the moisture inside the sample to dissipate to the outside, which broke the initial liquid phase environment, inhibited the sustainability of the hydration reaction, and was unfavorable to the improvement of the hydration rate.

[0075] 7. The particle size, mechanical properties and hydration rate of the product obtained by modifying the fluorine-containing gypsum with the polycarboxylic acid water-reducing agent in Comparative Example 2 were tested respectively, and the test results are shown in the following Tables 7 to 9.

[0076] [Table 7] Table 7: Particle size characterization of modified fluorine-containing gypsum at 0.3% polycarboxylic acid water reducer loading.

[0077] [Table 8] Table 8: Performance of modified fluorine-containing gypsum at 0.3% polycarboxylic acid water reducer loading

[0078] [Table 9] Table 9: Hydration rate of modified fluorine-containing gypsum when the amount of polycarboxylic acid water-reducing agent mixed is 0.3%

[0079] From Tables 7 to 9 above, it can be seen that polycarboxylic acids have high water-reducing efficiency and can play an obvious role in the grinding-assisted modification of fluorine-containing gypsum, but they have a restraint on the mechanical performance of the product obtained by the modification and a low hydration rate.

Claims

1. A step of co-grinding quicklime and fluorine-containing gypsum; further adding a naphthalene-based water reducing agent; A method for producing a modified fluorine-containing gypsum, comprising: The mass ratio of the quicklime to the fluorine-containing gypsum is (0.5 to 1.0):100, The mass ratio of the naphthalene-based water-reducing agent to the fluorine-containing gypsum is (0.3 to 0.9):100, The method for producing modified fluorine-containing gypsum, wherein the mixing and grinding time is 15 to 45 minutes.

2. The fluorine-containing gypsum is a by-product generated during the production of hydrogen fluoride, The fluorine-containing gypsum has a particle size of 0.3 to 1.5 cm, a pH value of 2.3, and a density of 2.59 g / cm 3 and 2. The method for producing modified fluorine-containing gypsum according to claim 1, wherein the main mineral composition of the fluorine-containing gypsum is type 2 anhydrite, and the fluorine-containing gypsum also contains fluorite.

3. The effective content of calcium oxide in the quicklime is 80 wt. % or more; 2. The method for producing modified fluorine-containing gypsum according to claim 1, wherein the naphthalene-based water reducing agent is a commercially available naphthalene-based water reducing agent.

4. A modified fluorine-containing gypsum, characterized in that the modified fluorine-containing gypsum is produced by the production method according to any one of claims 1 to 3.

5. A modified fluorine-containing gypsum product, characterized in that it is produced using the modified fluorine-containing gypsum according to claim 4.

6. 6. A method for producing the modified fluorine-containing gypsum product according to claim 5, comprising the steps of: (1) A step of uniformly mixing the modified fluorine-containing gypsum and water by stirring to obtain a modified fluorine-containing gypsum slurry; (2) putting the modified fluorine-containing gypsum slurry into a mold and curing it to obtain the modified fluorine-containing gypsum product; A method for producing a modified fluorine-containing gypsum product, comprising:

7. 7. The method for producing a modified fluorine-containing gypsum product according to claim 6, wherein the curing is performed at a temperature of 20±5° C. and a relative humidity of 70%±4%.

Citation Information

Patent Citations

  • Fluorgypsum modifying method and process for producing other chemical products by using fluorgypsum

    CN101979353A

  • Waste fluorine gypsum activating technique

    CN102020429A

  • Preparation method of phosphogypsum cementing material

    CN103466978A

  • Fluorogypsum-based multi-component composite light high-strength wall material and preparation method thereof

    CN108997023A

  • Modified phosphogypsum-based concrete prefabricated part and preparation method thereof

    CN111410499A